Teachers’ Strategies for Building Inclusive Classroom Environments in Social Studies: A Case Study of a Rural Indonesian School - Caterina Lo; Feby Meuthia Yusuf; Dedi Jasrial (AL-ISHLAH: Jurnal Pendidikan, 2025)
While numerous studies have examined teachers’ learning motivation and classroom management, limited research has focused on how educators foster inclusive classroom environments in rural contexts. This study investigates how teachers promote student motivation, comfort, and non-violence in Social Studies classrooms at a rural Junior High School in Siberut Utara, Mentawai Regency, West Sumatra, Indonesia. A qualitative case study approach was employed. Participants included two Social Sciences teachers across grades VII–IX and 26 students. Data were collected through direct classroom observations over nine sessions and semi-structured interviews with both teachers and selected students. Thematic analysis was used to identify key strategies implemented by teachers. Findings revealed that teachers enhanced student motivation using positive reinforcement, culturally relevant materials, and interactive teaching methods. To create a comfortable learning environment, teachers emphasized mutual respect, acknowledged cultural diversity, and offered emotional support. Strategies to reduce classroom violence included establishing clear behavioral expectations, integrating conflict resolution into the curriculum, and promoting inclusive dialogue during lessons. The study underscores the importance of contextually responsive teaching strategies in rural schools. By aligning pedagogy with students’ lived experiences and cultural backgrounds, teachers can foster a more inclusive, respectful, and effective learning environment. These findings provide valuable insights for educators working in similar rural contexts, enabling them to adopt inclusive strategies that support student engagement, emotional well-being, and positive classroom behavior.